2015
DOI: 10.1245/s10434-015-4591-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Breast Cancer in 2010–2011 SEER Registries by Hormone and HER2 Receptor Status

Abstract: Background Although locoregional recurrence is known to affect overall survival for operable breast cancer, the impact of receptor status on locoregional control is debated. Currently, hormone receptor (HR) and human epidermal growth factor receptor-2 (HER2) status are generally not considered relevant to surgical choice. This study examines recent population-level surgical trends with regard to receptor status. Methods We used the Surveillance, Epidemiology, and End Results (SEER) data to identify stage I–I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Patients with stage I-III HR+/HER2− BC underwent lumpectomy or mastectomy at rates of 71% and 25%, respectively, which demonstrates support for breast-conserving surgery comparable to [25] or greater than [26][27][28][29] that reported in other cohorts. Unfortunately, because systemic therapies can be entered into the ALR database as single agents and/or combination regimens and may be entered differently with each administration, it was prohibitively difficult to discern which regimens were given and for what duration.…”
Section: Treatmentsupporting
confidence: 57%
“…Patients with stage I-III HR+/HER2− BC underwent lumpectomy or mastectomy at rates of 71% and 25%, respectively, which demonstrates support for breast-conserving surgery comparable to [25] or greater than [26][27][28][29] that reported in other cohorts. Unfortunately, because systemic therapies can be entered into the ALR database as single agents and/or combination regimens and may be entered differently with each administration, it was prohibitively difficult to discern which regimens were given and for what duration.…”
Section: Treatmentsupporting
confidence: 57%
“…Younger black women were found to have more‐advanced disease but were equally likely to be diagnosed with TN breast cancer as older black women in the present study. Overall, 24·0 per cent of women were diagnosed with TN breast cancer, higher than the national rate of 12 per cent. Numerous previous studies have demonstrated disproportionately higher rates of TN breast cancer in black women and in young women overall.…”
Section: Discussionmentioning
confidence: 85%
“…A recent report of NSQIP data from 2005-2011 showed a relative increase in mastectomy of 2.9% per year during that time 13 . Additionally, the SEER database showed the mastectomy rate in 2011 was 46% 14 , which is roughly the same as the mastectomy rate in the MRG. Meanwhile, our control group mastectomy rate of 17.9% was quite low compared to the national average at that time (roughly 40%) 13 .…”
Section: Discussionmentioning
confidence: 70%